Bis(pentafluorophenyl)-o-carborane and its arylthio derivatives: synthesis, electrochemistry and optical properties. Issue 37 (19th August 2020) - Shida, Naoki; Owaki, Satoshi; Eguchi, Hiroshi; Nishikawa, Takanobu; Tomita, Ikuyoshi; Inagi, Shinsuke
Abstract : The synthesis of bis(pentafluorophenyl)- o -carborane is reported, which is further thiolated by nucleophilic aromatic substitution (SN Ar) reaction to give emissive materials in the solid state following aggregation-induced emission (AIE) fashion. Abstract : Synthesis of 1, 2-bis(pentafluorophenyl)- o -carborane and its arylthio-derivatives is reported. The regioselective arylthiolation was successfully achieved via nucleophilic aromatic substitution (SN Ar) reaction. A series of bis(perfluoroaryl)- o -carboranes with various para -substituents showed strong multicolor emission in the solid-state ( Φ f up to 47%), suggesting an aggregation-induced emission (AIE) character in this motif.